Genotyping of Interleukin-1B SNPs in Correlation with Coronary Heart Disease associated Gingivitis - Fatima Malik Abood (Journal of Global Pharma Technology, 2017)
Objective: Designed to detect most important bacteria implicated gingivitis associated coronary heart disease and investigate interleukin-1 beta gene polymorphism (SNPs) and their possible role with CHD cases with and without chronic gingivitis at positions IL-1????-13 and IL-1????-511.Background: Coronary heart disease is impaired blood flow in the arteries that supply blood to the heart. Methods: Study subjects consisted of 40 (22 males and 18 females with 45-76 year old, mean 63±6.18) and 30 control (18 males and 12 females) who were gingivitis free, from each subject 2 specimens (swab for bacterial isolation and 5mm of venous blood were taken in EDTA tubes for DNA extraction.IL-1B-31 and IL-1B-511SNPs were amplified by PCR and DNA products sequenced in Gen Bank (Gen Bank accession number NC-000009.11) and scanned for detecting IL-1B-31 and IL-1B-511SNPs. Results: bacteriological study was showed the dominant bacteria in patients were viridians streptococcus, staphylococcus aureus, black pigmented bacteria and candida. The numbers of theses bacteria in patients were higher than control. Genetic study showed three genotypes for -13IL-1B SNP among patients; CC, CT and TT were 29 (72%), 8 (20%) and 3 (7.5%) respectively, However, only two genotypes among control; CC: (27(90) and TT: (3(10), with no significance differences between patients and control (OR= 0.9 (0.87–1.07). While only two genotypes for -115IL-1B SNP among patients; CC: 31 (77.5%) and CT: 9 (22.5%). However, in both SNPs C allele frequency was (dominant) among patients and control. With significance differences p≤ 0.05) (OR=2.829, 95%CI), (OR=1.0(0.85–1.17) respectively, Conclusion: the presence of theses bacteria and SNPs at position -511and -13 of IL1B gene are associated with the severity of CHD with gingivitis and may affect the secretion of IL1B cytokine.